1997
DOI: 10.1109/57.591529
|View full text |Cite
|
Sign up to set email alerts
|

Space charge measurements on impregnated paper: a review of the PEA method and a discussion of results

Abstract: Quantitative knowledge about space charge inside electrical insulation is important in order to evaluate t h e electrical field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(49 citation statements)
references
References 10 publications
0
45
0
Order By: Relevance
“…50,52 This sensitive method is of high resolution, 53 with its basic principles can be found elsewhere. 50,54 The amplitude of measurement results is proportional to the density of charge, with its polarity straightforward denotes the polarity of charge, and the delay is related to the position of charge.…”
Section: Experimental Proof Of Ion Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…50,52 This sensitive method is of high resolution, 53 with its basic principles can be found elsewhere. 50,54 The amplitude of measurement results is proportional to the density of charge, with its polarity straightforward denotes the polarity of charge, and the delay is related to the position of charge.…”
Section: Experimental Proof Of Ion Migrationmentioning
confidence: 99%
“…one-dimensional distribution, which is the prerequisite for performing PEA test. [50][51][52] In the quasi-bicrystal samples, the intergranular layer contains Bi, Mn and Co elements for acquiring excellent electrical nonlinearity (fabrication procedures of quasi-bicrystal are directed to Ref. 6).…”
Section: Experimental Proof Of Ion Migrationmentioning
confidence: 99%
“…Hence there was evident homocharge accumulation near the anode. As regards heterocharge accumulation inner specimens with higher moisture concentrations, it was firstly reported in 1997 [18]. It was thought to be caused by the influence of moisture on carriers' movement and dielectric polarization then.…”
Section: Space Charge Measurementmentioning
confidence: 99%
“…But there is still no complete explanation so far and more investigation is required. It is generally accepted that moisture can accelerate space charge accumulation within oil paper [18], but the moisture concentration is usually less than 5%. Fig.…”
Section: Space Charge Measurementmentioning
confidence: 99%
“…Partial discharge or breakdown may occur in those places where the electrical field strength is strengthened; this can lead to premature failure of the insulation material (Zhang et al 1996;Liu et al 1989). To date, research has focused on the space charge dynamics of oil-impregnated insulation paper affected by voltage level, temperature, and moisture (Morshuis and Jeroense 1997;Ciobanu et al 2002;Tang et al 2010;Zhou et al 2009;Liu et al 1998). Although studies have found that many nanoparticles improve the space charge distribution in insulation materials such as polyethylene and polyimide, there are no reports on how to improve the space charge distribution in oil-impregnated insulation paper (Fleming et al 2005;Huang et al 2009;Wang et al 2009;Zha et al 2010;Thelakkadan et al 2011;Abd El-kader et al 2009;Ahmad et al 1992).…”
Section: Introductionmentioning
confidence: 99%